HUBUNGAN SKOR PUFA/pufa DENGAN INDEKS MASSA TUBUH PADA ANAK USIA 6 – 12 TAHUN DI SD IT AL – AZHAR 2 BATAM - Rusdani, Rusdani (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2018)
The Correlation between PUFA/pufa Score with Body Mass Index in Children Aged 6 – 12 years at Elementary School of Integrated Islamic Al-Azhar 2 Batam. Mini  Thesis. Faculty of Medicine, Batam University. Dental caries problems in elementary school-aged children are important because dental caries is an indicator of successful dental health maintenance of children. In 2010, Monse et al. introduced the PUFA/pufa score to assess the severity of dental caries that was treated in permanent teeth (PUFA) and deciduous teeth (pufa). Benzian et al. stated that BMI is related to the prevalence of caries-induced odontogenic infection (PUFA/pufa), seen in 55.7% of children with PUFA/pufa 27.1% of whom had a BMI below normal and 1% had a BMI above normal. Referring to this fact, the researcher is interested to examine the correlation of PUFA/pufa score with body mass index in children aged 6-12 years atElementary School of Integrated Islamic Al-Azhar 2 Batam. This research is analytic type of observation with cross-sectional method. The population of this study is all student with a population of 136 children and by using purposive sampling technique obtained a sample of 121 people. Data obtained by measuring body weight, height and assessing tooth decay, missing, or that have been replaced. The data obtained were processed statistically with SPSS using Chi-Square test. The result of this study indicate that there is a significant relationship between PUFA/pufa score with body mass index. Based on the results of bivariate analysis Chi-Square test obtained p value 0.003 (Significant). In the category of children who have a  PUFA/pufa score of ³1 SD obtained a child whose BMI is lean – very thin as many as 18 (72.0%) children and children who have normal BMI – very fat as many as 7 (28.0%) children. There is a significant between PUFA/pufa scorewith body mass index in children aged 6-12 years atElementary School of Integrated Islamic Al-Azhar 2